Wii‐based exercise program to improve physical fitness, motor proficiency and functional mobility in adults with Down syndrome. Issue 8 (6th June 2017) - Silva, V.; Campos, C.; Sá, A.; Cavadas, M.; Pinto, J.; Simões, P.; Machado, S.; Murillo‐Rodríguez, E.; Barbosa‐Rocha, N.
Abstract: Background: People with Down syndrome (DS) usually display reduced physical fitness (aerobic capacity, muscle strength and abnormal body composition), motor proficiency impairments (balance and postural control) and physical functional limitations. Exergames can be an appealing alternative to enhance exercise engagement and compliance, whilst improving physical fitness and motor function. This study aims to analyse the effects of a Wii‐based exercise program on physical fitness, functional mobility and motor proficiency of adults with DS. Methods: Twenty‐seven adults with DS were randomly allocated to an experimental group (Wii; n = 14) or control group ( n = 13). Participants in the experimental group completed a 2‐month Wii‐based exercise program, with three 1‐h sessions per week that included training games for aerobic endurance, balance and isometric strength. Participants completed assessments regarding anthropometric measures, physical fitness, functional mobility and motor proficiency. Results: Mixed ANOVA analysis showed a significant group by time interaction for aerobic endurance, explosive leg power and flexibility. Independent samples t ‐test for change scores indicated significant between‐group differences favouring the experimental group regarding speed of limb movement, trunk strength and functional mobility, as well as a trend towards significance on body weight. Mann–Whitney's U test for change scores demonstrated between‐group differences favouring the experimental group for visceral fat as well as running speed and agility. Large within‐group effect sizes were observed for explosive leg power ( d = 1.691), body weight ( d = 1.281), functional mobility ( d = 1.218), aerobic endurance ( d = 1.020), speed of limb movement ( d = 0.867) and flexibility ( d = 0.818) in the experimental group. Conclusions: Our findings suggest that Wii‐based exercise can be an effective tool to improve physical fitness, functional mobility and motor proficiency of adults with DS, including crucial measures such as aerobic capacity and lower limb strength. Exergames using Wii Fit or other equipment can be appealing alternatives for adults with DS to engage in regular physical activity, preventing sedentary behaviour and decreasing the risk to develop cardiovascular diseases.